ACCENT VARIATION IN THE UENO FAMILY YOUTUBE CHANNEL - Rosmita Ambarita; Rahmad Huda; Vera Kristiana (Fakultas Sastra UMN AL Washliyah, 2026)
Language variation, particularly in accent, reflects how cultural and linguistic backgrounds shape communication. This study aims to analyze accent variation used by the members of the Ueno Family in their YouTube channel as a reflection of bilingual interaction and identity. Using a qualitative descriptive method, the data were obtained from several vlog episodes through observation and transcription, focusing on pronunciation, intonation, and accent interference. The results show that the Japanese father demonstrates Japanese accent characteristics when speaking Indonesian, such as vowel length and /r/ articulation, while the Indonesian mother displays traces of Indonesian accent when speaking English. These findings indicate that accent variation in the Ueno Family vlog not only represents linguistic differences but also reveals how language functions as a marker of cultural identity in a multilingual and digital context.